Stability and adaptability of grain yield in quinoa genotypes in four locations of Iran - Jokarfard, Vahid; Rabiei, Babak; Laki, Ebrahim Souri; Börner, Andreas (Frontiers in Plant Science, 2024)
The genotype × environment interaction is one of the effective factors in identifying and introducing cultivars with stable grain yield in different environments. There are many statistical methods for estimating genotype × environment interaction, among which AMMI and GGE-biplot analyses provide better and more interpretable results. The objective of this study was to assess the genotype × environment interaction, as well as the adaptability and stability of 40 quinoa genotypes. The experiment was carried out in a randomized complete block design with three replications in eight environments (four locations of Iran and two years). The AMMI analysis of variance showed that the main effects of genotype and environment, as well as the interaction effect of genotype × environment were significant on grain yield. Separation of genotype × environment interaction based on the principal component method showed that the first six principal components were significant and accounted for 47.6%, 22.5%, 9%, 7%, 6% and 4.3% of the genotype × environment interaction variance, respectively. Based on the AMMI model, genotypes G16, G19, G35, G30, G39, G24, and G18 were identified as high-yielding and stable genotypes with high general adaptability. In contrast, genotypes G36, G27, G38, G9, G28, G29, G23, G34, G13, and G12 were the most unstable genotypes in the studied environments. In GGE-biplot analysis, two megaenvironments were identified, and genotypes G16, G19, G25, and G17 were also identified as high-yielding and stable genotypes for these environments. Also, based on the biplot diagram of the ideal genotype, genotypes G16 ، G19, G17, and G35 were the nearest genotypes to the ideal genotype. In total, the results of various analyses showed that the three genotypes G16 and G19 were the superior genotypes of this experiment in terms of grain yield and stability. These genotypes can be introduced as high-yielding and stable genotypes to the climatic conditions of the studied areas.